Role of Adaptive Immunity in Alcoholic Liver Disease - Emanuele Albano (International Journal of Hepatology)
Stimulation of innate immunity is increasingly recognized to play an important role in the pathogenesis of alcoholic liver disease (ALD), while the contribution of adaptive immunity has received less attention. Clinical and experimental data show the involvement of Th-1 and Th-17 T-lymphocytes in alcoholic hepatitis. Nonetheless, the mechanisms by which alcohol triggers adaptive immunity are still incompletely characterized. Patients with advanced ALD have circulating IgG and T-lymphocytes recognizing epitopes derived from protein modification by hydroxyethyl free radicals and end products of lipid-peroxidation. High titers of IgG against lipid peroxidation-derived antigens are associated with an increased hepatic production of proinflammatory cytokines/chemokines. Moreover, the same antigens favor the breaking of self-tolerance towards liver constituents. In particular, autoantibodies against cytochrome P4502E1 (CYP2E1) are evident in a subset of ALD patients. Altogether these results suggest that allo- and autoimmune reactions triggered by oxidative stress might contribute to hepatic inflammation during the progression of ALD.